Revision of the Athyrisininae, Siluro-Devonian brachiopods from China and Russia - Jia-Yu, R (戎嘉余); Alvarez, F; Modzalevskaya, TL; Yan, Z (WILEY-BLACKWELL, 2004)
Athyrisinine brachiopods from the Upper Silurian of Russia and the Lower-Middle Devonian of China and north Vietnam include over 70 species belonging to Athyrisina and Parathyrisina; generic and subfamilial diagnoses are emended. Five genera are considered synonyms of Athyrisina and three of Parathyrisina. A neotype is selected and illustrated for Athyrisina squamosa, the type species of Athyrisina. Four nomina nova, Athyrisinaxui, Parathyrisina wani, P. minima, and P. cheni, are suggested as new substitute names for Athyrisina tumida Wang, in Xu et al. 1978 (primary homonymy), Athyrisinoides ganxiensis Wan, in Xu et al. 1978, Parathyrisina minor Zhang, in Zhang and Fu 1983, and Athyrisinoides tudilingensis Chen, 1979 (secondary homonyms) respectively. A new genus, Bruntosina, is described from the Emsian to Eifelian of the Qinling region. A new subfamily, Homeathyridinae, is erected within the Athyrididae with Homeathyris, Pseudohomeospira, and Squamathyris included, revised and their diagnoses emended. Homeathyris incisus sp. nov. is described from the Ludfordian of Novaya Zemlya. Ikella is revised and excluded from the athyrisinins. The origin and dispersal of the homeathyridins and the athyrisinins are discussed.